Sensors as tactile technique in ultrasonic cleaning reactor / Muhammad Izzuan Asarozi - Asarozi, Muhammad Izzuan (2019)
An “ideal sensor” which is robust enough to withstand bubble jetting is proposed. Such sensor could be used to investigate temperature, pressure and acoustic pressure of water which can be used to measure cavitation effects, generated by ultrasound. In this experiment, DS18B20 Digital Temperature Sensor, MAX4466 Hydrophone Amplifier and SKU 237585 Pressure Transducer Sensor were connected to Arduino Uno to form sensors systems which were tested at 3 different depths namely at the bottom (0 cm), at the middle (3.5 cm) and at the top of a beaker (7.5 cm), to determine the performance of the sensors. Based on the result, DS18B20 Temperature Sensors provided consistent readings as the standard deviation was in between 0.08 to 0.38 which was less than 1% from the average values. However, SKU237585 pressure transducer sensor gave inconsistent readings as the standard deviation was more than 1% which was 0.01 to 0.56 from the average values. The result also showed MAX4466 Hydrophone Amplifier was insufficient to detect the acoustic emission signal due to its’ small bandwidth. In addition, the temperature and negative of pressure at the bottom of container produced the highest reading compared at the top and the middle similar to the study conducted by other researchers.